Stage‐ and thermal‐specific genetic architecture for preadult viability in natural populations of Drosophila melanogaster - Petino Zappala, María Alejandra; Satorre, Ignacio; Fanara, Juan Jose (Journal of evolutionary biology, 2019)
Studying the processes affecting variation for preadult viability is essential to understand the evolutionary trajectories followed by natural populations. This task requires focusing on the complex nature of the phenotype-genotype relationship by taking into account usually neglected aspects of the phenotype and recognizing the modularity between different ontogenetic stages. Here, we describe phenotypic variability for viability during the larval and pupal stages in lines derived from three natural populations of Drosophila melanogaster, as well as the variability for phenotypic plasticity and canalization at two different rearing temperatures. The results indicate that the three populations present significant phenotypic differences for preadult viability. Furthermore, distinct aspects of the phenotype (means, plasticity, canalization, plasticity of canalization) are affected by different genetic bases underlying changes in viability in a stage‐ and environment‐specific manner. These findings explain the generalized maintenance of genetic variability for this fitness trait.
Gesehen am 09.02.2026